2019
DOI: 10.1002/solr.201970061
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Cost, High‐Efficiency, and Efficiency Predictable Small Molecule Organic Dyes with Bis(4‐styryl)phenyl Amino Donor for Dye‐Sensitized Solar Cells (Solar RRL 6∕2019)

Abstract: In article no. http://doi.wiley.com/10.1002/solr.201900066, Aiying Pang, Guang Shao, Yingjun Zhang, Jing‐Kun Fang, and co‐workers report three small molecule organic dyes (SMODs). For these SMODs, a linear correlation between the dipole moments (μ) and power conversion efficiency (η) are observed to be η = 0.817μ − 0.370 with R2 = 0.999. This allows for a facile way to predict the power conversion efficiency of dyes with similar molecular structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…However, in the AN13/perovskite films, grain sizes larger than 200 nm were rarely observed, and the grain size appeared to have reduced (average 96 nm). In perovskite crystals, grain boundaries are known to provide trap sites for charges, which is disadvantageous in terms of charge transfer [60][61][62]. Therefore, we confirmed that AN11 samples were optimized for the smooth operation of perovskite photovoltaic cells and could also be advantageously used for perovskite crystal formation compared to AN10 and AN13.…”
Section: Degree Of Polymerization 2supporting
confidence: 64%
“…However, in the AN13/perovskite films, grain sizes larger than 200 nm were rarely observed, and the grain size appeared to have reduced (average 96 nm). In perovskite crystals, grain boundaries are known to provide trap sites for charges, which is disadvantageous in terms of charge transfer [60][61][62]. Therefore, we confirmed that AN11 samples were optimized for the smooth operation of perovskite photovoltaic cells and could also be advantageously used for perovskite crystal formation compared to AN10 and AN13.…”
Section: Degree Of Polymerization 2supporting
confidence: 64%